Unravelling Charge Storage Mechanisms of Lithium, Sodium and Potassium into Graphene‐Coffee Waste Derived Hard Carbon Composites. Issue 3 (9th January 2023) - Gómez‐Urbano, Juan Luis; Leibing, Christian; Jauregui, María; Darlami‐Magar, Sandesh; Saurel, Damien; Carriazo, Daniel; Balducci, Andrea
Abstract: Hard carbons are promising anode materials for lithium, sodium and potassium‐ion batteries attending to their low cost, simple processing technology and outstanding electrochemical performance. However, their complex structure and controversial carrier‐ion storage mechanisms makes difficult the prediction of their performance. Herein, we investigate the insertion storage mechanisms behind of three different alkali metal ions (lithium, sodium and potassium) into a hard carbon composite obtained by the pyrolysis of coffee waste and graphene oxide. The insertion/deinsertion processes have been monitored by galvanostatic intermittent titration technique and operando X‐Ray diffraction. Results reveal that alkaline metal ions follow an adsorption‐intercalation mechanism where the high potential region can be ascribed to the adsorption of the alkaline metal ions on the surface active sites, while slopping region arises from their intercalation between the pseudo‐graphitic micro‐crystallites. Moreover, the graphene‐coffee waste hard carbon exhibits a notorious capacity retention after 300 charge/discharge cycles in all the alkaline metals evaluated. Abstract : How the metal ions inserted : The insertion storage of lithium, sodium and potassium ions in a graphene‐biowaste derived hard carbon are studied by operando XRD and GITT techniques, revealing that alkaline metal ions follow an adsorption‐intercalation mechanism. Moreover, the hard composite shows a remarkable capacity retention upon cycling.